2000
DOI: 10.1074/jbc.m000577200
|View full text |Cite
|
Sign up to set email alerts
|

Stopped-flow Reaction Kinetics of Recombinant Components of Proton-translocating Transhydrogenase with Physiological Nucleotides

Abstract: Transhydrogenase, which is found in the inner membranes of animal mitochondria and the cytoplasmic membranes of some bacteria, catalyzes the reaction shown below.A single proton is translocated across the membrane, from the p-aqueous phase (the "outside" of intact mitochondria and bacteria) to the n-aqueous phase (the "inside"), for each hydride equivalent transferred from NADH to NADP ϩ . Under most conditions, this is the in vivo direction; the reaction is driven by the proton electrochemical gradient (⌬p) r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(42 citation statements)
references
References 37 publications
(92 reference statements)
1
41
0
Order By: Relevance
“…Motion of domain III within TH is described in terms of 'open' and 'occluded' states in the 'alternating site, binding change mechanism' (11). Based on kinetic data for the heterotrimeric complex in solution (24,31), the cocrystal structure with NADP bound to domain III, e.g., Figure 7, corresponds to the 'occluded' state (11). Recently, a conserved acidic residue ( Asp213) in an extramembranous loop of domain II of E. coli TH has been found to be required for proton translocation, suggesting a mechanism by which NADPH-induced movement of domain III could affect a pK a shift in domain II, which in turn would favor proton translocation (36).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Motion of domain III within TH is described in terms of 'open' and 'occluded' states in the 'alternating site, binding change mechanism' (11). Based on kinetic data for the heterotrimeric complex in solution (24,31), the cocrystal structure with NADP bound to domain III, e.g., Figure 7, corresponds to the 'occluded' state (11). Recently, a conserved acidic residue ( Asp213) in an extramembranous loop of domain II of E. coli TH has been found to be required for proton translocation, suggesting a mechanism by which NADPH-induced movement of domain III could affect a pK a shift in domain II, which in turn would favor proton translocation (36).…”
Section: Discussionmentioning
confidence: 99%
“…Kinetic experiments have defined two states for bound NADH, one with a K d of ∼30 µM, and one with a K d of ∼300 µM (24,25). These binding constants are interpreted as corresponding to favorable binding when domain I is associated with domain III (with NADP bound) in the 'open' state, and weaker binding when domain III is converted to the 'occluded' state prior to rapid hydride transfer (11).…”
Section: Nadh-containing Crystalsmentioning
confidence: 99%
“…Thus, the basic mechanism is (i) substrate nucleotides, NADP + and NADH, associate with their binding sites in an enzyme protomer having both dIII and dI in open states, (ii) protonation of dII from the outside aqueous phase converts the open dIII to occluded, (iii) hydride-ion equivalents are transferred from bound NADH to NADP + , (iv) deprotonation of dII on the cytoplasmic side regenerates the open state of dIII, and (v) the nucleotide products, NADPH and NAD + , are released. The binding affinities of NAD + and NADH to dI are not significantly altered during the catalytic cycle; this enzyme component remains open except perhaps during the brief (<10 À3 s) period of hydride transfer [23,56]. The proposed mechanism affords two important features.…”
Section: The Binding-change Mechanism Of Coupling To Proton Translocamentioning
confidence: 93%
“…Following experiments to characterize the hydride transfer reaction between NADPH and NAD ϩ in mixtures of dI and dIII, we showed that the value of the rate constant for product NADH release, measured using isolated dI, was inconsistent with the simple kinetic scheme (34). It was suggested that the rate constant for NADH release from the complex of dI and dIII must be much greater than that for isolated dI protein.…”
Section: Alternating Sites Of Proton-translocating Transhydrogenasementioning
confidence: 95%
“…However, assuming that the binding capacity of the low affinity site is 1.0/mol of dI 2 dIII 1 , the data fitted to a K d ϭ 311 Ϯ 91 M and an enthalpy change of Ϫ79.4 kJ⅐mol Ϫ1 of dI 2 dIII 1 . In recent stopped-flow experiments, we recorded the kinetics of the fluorescence quenching of the (single) Trp 72 in dI during NADH binding (34); the objective was to determine the k on and k off for that nucleotide-binding step. We noted that the amplitude of the dI fluorescence quenching was decreased when dIII.NADPH was present (the wild-type dIII protein, with no Trp residues, was used).…”
Section: Alternating Sites Of Proton-translocating Transhydrogenasementioning
confidence: 99%